Voices of Women With Lived Experience of Substance Use During Pregnancy: A Qualitative Study of Motivators and Barriers to Recruitment and Retention in Research. Issue 1 (January 2023) - Hilliard, Florence; Goldstein, Ellen; Nervik, Kendra; Croes, Kenneth; Ossorio, Pilar N.; Zgierska, Aleksandra E.
Abstract : Despite concerns about negative neurocognitive effects of in utero substance exposure on child and brain development, research in this area is limited. This study gathered perspectives of persons with lived experience of substance use (eg, alcohol, prescription and illicit opioids, and other illicit substances) during a previous pregnancy to determine facilitators and barriers to research engagement in this vulnerable population. We conducted structured, in-depth, individual interviews and 2 focus groups of adult persons with lived experience of substance use during a previous pregnancy. Questions were developed by clinical, research, bioethics, and legal experts, with input from diverse stakeholders. They inquired about facilitators and barriers to research recruitment and retention, especially in long-term studies, with attention to bio-sample and neuroimaging data collection and legal issues. Interviews and focus groups were audio-recorded, transcribed, and analyzed using inductive coding qualitative analysis methods. Ten participants completed in-depth interviews and 7 participated in focus groups. Three main themes emerged as potential barriers to research engagement: shame of using drugs while pregnant, fear of punitive action, and mistrust of health care and research professionals. Facilitative factors included trustworthiness, compassion, and a nonjudgmental attitude among research personnel. Inclusion of gender-concordant recovery peer support specialists as research team members was the most frequently identified facilitator important for helping participants reduce fears and bolster trust in research personnel. In this qualitative study, persons with lived experience of substance use during a previous pregnancy identified factors critical for engaging this population in research, emphasizing the involvement of peer support specialists as research team members.